Islamic moderation (Wasatiyyah) manifestation of practices: an elaboration of its degree of effectiveness - Hj. Yaakub, Muhamadul Bakir; Othman, Khatijah; Nik Nazli, Nik Nadian Nisa (Gyandhara International Academic Publications, 2019)
Purpose: The study is an attempt to elaborate on students' development explicitly, understanding and practices of Islamic Moderation Personality (IMP) in Malaysian Higher Learning Institution (MHLI). The measurement of the development of their understanding, especially in term of its representation of IMP is underlined. Based on this measurement, personal conceptual beliefs, understanding principles in life and the manifestation of IMP able to make a person different compared to others. In this article, the cause of differences is measured by comparing the intensity of IM practices and the manifestation types and patterns. Methodology: The method used in this study is a quantitative methodology, and by using the questionnaires, the survey has been conducted to 508 respondents in six MHLIs. The data analysis was performed using Structural Equation Modelling (SEM) method with the help of AMOS software version 23. Results: The survey administered to the students of MHLI showed a higher level of IMP manifestation expressed by their self-conceptual understanding and attitudinal paradigm through attitude to Allah SWT, attitude to own-self, and attitude to others. These strongly contributed to self-satisfaction personality in achieving awareness, perfection, and reasonable state of balanced and robust willingness. Simultaneously, item practices acted as a mediator between Islamic moderation conceptual paradigm and its manifestation practices. Implications: The finding provides a foundation for further research in IMP manifestation, both as a general principle in life and specific domains such as religion, education, and socialization practices.Hence, IM as a complete balanced system in life should be adopted and practiced accurately and precisely according to the revelation sources.